Theory of Mind Performance Predicts tDCS-Mediated Effects on the Medial Prefrontal Cortex: A Pilot Study to Investigate the Role of Sex and Age - Cotelli, Maria (Brain Sci, 2020)
Transcranial Direct Current Stimulation (tDCS) has become an increasingly promising tool for understanding the relationship between brain and behavior. The purpose of this study was to investigate whether the magnitude of sex- and age-related tDCS effects previously found in the medial prefrontal cortex (mPFC) during a Theory of Mind (ToM) task correlates with social cognition performance; in particular, we explored whether different patterns of activity would be detected in high- and low-performing participants. For this, young and elderly, male and female participants were categorized as a low- or high-performer according to their score on the Reading the Mind in the Eyes task. Furthermore, we explored whether sex- and age-related effects associated with active tDCS on the mPFC were related to cognitive functioning. We observed the following results: (i) elderly participants experience a significant decline in ToM performance compared to young participants; (ii) low-performing elderly females report slowing of reaction time when anodal tDCS is applied over the mPFC during a ToM task; and (iii) low-performing elderly females are characterized by lower scores in executive control functions, verbal fluency and verbal short-term memory. The relationship between tDCS results and cognitive functioning is discussed in light of the neuroscientific literature on sex- and age-related differences.